The FGF Family in Humans, Mice, and Zebrafish: Development, Physiology, and Pathophysiology - Sasaki, Sayaka; Ohta, Hiroya; Nakajima, Yoshiaki; Konishi, Morichika; Miyake, Ayumi; Itoh, Nobuyuki (IntechOpen, 2011)
None